Pertanggung Jawaban Pelaku Tindak Pidana Perjudian Online di Indonesia - Rodhiyah, Isyatur; Hapsari, Ifahda Pratama; Iskandar, Hardian Iskandar (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2022)
The criminal act of gambling is a crime that is commonly committed by many people, because from gambling people can get multiple wealth from the results of gambling. In Indonesia, the practice of gambling has developed along with the development of technological advances, namely online gambling. This online gambling crime offers many advantages for owners and managers, because in practice the online gambling business scheme no longer requires complicated permits to establish a gambling business via the internet. Based on these conditions, this study wants to explain that Indonesia has legally regulated gambling in several laws and regulations, including those regulated in Article 303 and Article 303 bis of the Criminal Code. Then related to online gambling laws specifically regulated in Article 27 paragraph (2) of the Electronic Transaction Information Law and its amendments. The use of normative legal methods with a statutory approach (staapproach) is carried out carefully by examining and analyzing legal rules relating to the accountability of online gambling crimes in Indonesia. The responsibility of online gambling actors is proven by containing elements of a criminal act. The criminal responsibility of online gambling actors is not only borne by players, but also includes those who give someone the opportunity to play gambling, such as service providers and managers of online gambling platforms.